The Emperor's hip clothes and the fat boy slim's dream how fashion and fitness affect the communication levels of the UP college students - Chukhant, Arunee Sheryl D.
This study focused on how fashion and fitness affect the communication levels of the UP college students. It aimed to determine how these group of people regard their self-concept in terms of fashion and in terms of fitness, to determine the factors which influence their concept of fashion and their view of fitness, and to explain how the said components of physical appearance affect people's perception of themselves. At the interpersonal level, the study aimed to explore how college students interact with fashionable and fit people, and also to understand how these people were persuaded and influenced by fashion, and fitness leaders. At the mass communication level, it seeks to find out the college students' adoption or rejection of fitness and fashion innovations and trends. There are five theories that are used in the study. The following are the 1. Social Construction or Self, 2. Social Learning Theory, 3. Face Negotiation Theory, 4. Symbolic Interactionism, and 5. Innovation Diffusion. Since this research is a multi-method study, it has utilized three research methods, namely 1. The survey for the quantitative approach, 2. Focus interview and 3. Focus group discussion for the qualitative approach. The major findings of this research were the following: at the intrapersonal level of communication: the people naturally, notice the physical body and clothing through social initial contacts. Fashion was, basically, defined as the way of dressing up while fitness is mainly for health purposes. At the interpersonal level, college students perceive fashion and fitness as cue to the personalities of other people although not to the extent of telling the totality of a person. This in turn, gauge their attitudes in interacting and communicating with these people. Compliments may not motivate individuals with that of the motivation obtained from criticisms. In this manner, criticisms are taken as a positive remark for self-awareness and improvement. At the mass communication level, the mass media is still a potent agency of fashion and fitness innovations and adoptions. The media equates being fit and fashionable to being beautiful and desirable. Its impact to the audience is very visible on the college students' conformity to trends. However, the informants do not agree in the imposing and dictating power of mass media. College students believe that fashion and fitness in the mass media also miseducate the Filipino youth and children. More so, Western fashion proliferates in the Philippine mass media while the Filipino ingenuity in fashion is scarcely promoted.